Teoria da mutação constitucional: limites e possibilidades das mudanças informais da constituição a partir da teoria da concretização - Pedra, Adriano Sant'Ana (2009)
The objective of this study is to analyze the informal constitutional changes and to further examine the limitations to which they are submitted. In opposition to what occurs with formal changes (constitutional amendments), informal changes are not foreseen by the Constitution. Nevertheless, constitutional changes occur and are necessary as means of preservation and conservation of the Constitution, purposing its perfection, and seeking, through a dialectical process, to attain harmony with society. This is due to the fact that constitutional norms are not to be considered perfect and complete, but are yet in a constant state of mutual interaction with reality. There is no systematic treatment related to the limitations to which constitutional mutations submit existing in fact a shortage of works that deal specifically with the theme. The proposed hypothesis is that constitutional mutation must occur within the limits set by the normative force and by the supremacy of the Constitution itself. For the development of this work, it is necessary to consider that the constitutional norm does not confound with the Constitution text, but it is the result of a concretion process, methodologically structured. According to the concretion theory, constitutional norms result from the connection between the normative program (Normprogram), that is, its literal expression, and the normative ambit (Normbereich), understood by the surrounding reality, which results in a decision norm. Constitutional mutations occur from the existing alterations in the normative ambit and contained by the concretion process. The followed methodological approach proposes the analysis of legitimate ways for constitutional mutations to occur. Through deductive process, the informal constitutional changes that may be contained by the normative program, by the normative ambit and by the decision norm are analyzed. The applied research technique is the bibliographic research, jurisprudential and legislative. The obtained results with the research enables us to evaluate the limitations that are imposed to constitutional mutations, as well as associating them to the elements that integrate the norm. The identified and analyzed limits in this work are the elasticity of the text, the binding orders of the Constitutional Court, the prohibition of abolition of perpetual clauses, the prohibition retreating to fundamental rights and writs (normative program), the transcending restrictions, the legitimate acceptance by the community (normative ambit), the rationality of the decisions, the authority conferred to another institution and the non-retroactivity of the effects of the new interpretation (decision norm)